RISK MANAGEMENT AT MI AS-SHOLIHIN KARANGPENANG OLOH KARANGPENANG SAMPANG - Muzayyin, Muzayyin; Mundiri, Akmal; Mushfi El Iq Bali, Muhammad; Rozi, Fathor; Muali, Chusnul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
In the world of education, of course there are several factors that can influence the development of an educational institution, one of which is risk. The existence of a risk can certainly have a negative impact on the development of an educational institution. but this risk cannot be simply avoided, the risk can be managed or controlled, so that it does not have such a big impact. therefore in an institution it is necessary to have a management or so-called Risk Management, which is used to identify, measure, control and evaluate the risks created from the implementation of educational programs. so that in this study the aim was to find out how to implement risk management in the educational program at MI MMU As-Sholihin Karangpenang Oloh Sampang. The method used is a qualitative method in which obtaining data an interview was conducted with the school and then the results of the interview were discussed together so that a conclusion was obtained that the risks found at MI MMU As-Sholihin Karangpenang Oloh Sampang consisted of internal risks and external risks, where the internal factors found were facilities and infrastructure that were not in good condition, lack of teaching staff who were competent in their fields, teacher welfare that was not paid enough attention to, then from external factors was a lack of support society towards educational institutions and the lack of regeneration of alumni. the stages of risk management at MI MMU As-Sholihin Karangpenang Oloh Sampang include identifying problems where they are identified by analyzing and monitoring internal and external factors. Measuring risk is carried out through development diagrams of educational institutions and the last one is evaluating the risks carried out in various ways such as discussions, meetings and so on, in which it is discussed what methods or steps can be taken from the risks that have been identified in the previous stages